Addressing gambling harms by reducing the supply of electronic gambling machines: a comparative study of Italy and Finland - Virve Marionneau; Gabriele Mandolesi; Sara Rolando; Janne Nikkinen (BMC, 2022)
Abstract Background Electronic gambling machines (EGMs) are amongst the most harmful forms of gambling. The high availability of EGMs is also linked to increased consumption. To reduce the burden of EGMs on public health, policies to reduce their numbers have recently been introduced in Italy and Finland. This study compares the aims and justifications of these legislative changes, as well as their overall impacts on total consumption. Methods The objectives and justifications of policies to reduce the number of EGMs were based on qualitative media analysis. The impacts on total consumption were measured using financial figures provided by gambling providers in Italy and Finland. Results Results show that the reductions in EGM numbers were justified in terms of public health concerns in both countries, but the amplitude of policies varied. In Italy, the reductions were more ambitious than in Finland, and included reductions in the number of gambling locations. The financial data nevertheless indicated that the reductions may not have been significant enough. Conclusions Public health concerns were initially highlighted in the media discussions, but eventually in both countries reduction policies were less ambitious due to industry lobbying and state revenue interests. The reductions therefore do not appear to have been effective in reducing total consumption and the burden on public health.